2022
DOI: 10.1111/ijfs.15871
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of yeast β‐glucan on thermal aggregation and flavour adsorption capacity of Spanish mackerel myosin

Abstract: The effects of yeast β-glucan (YG) on the aggregation and flavour adsorption capacity of Spanish mackerel myosin under two-step heat treatments were investigated. The surface hydrophobicity and active sulfhydryl content of heat-induced myosin was increased by the addition of YG, reaching the maximum values of 81.46 and 17.49 mol per 10 5 g after heating at 90 °C for 10 min. YG incorporation significantly decreased the α-helix content of myosin to the minimum value of 48.27%, whereas the β-sheet was increased. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The total SH content significantly decreased after adding OG ( P < 0.05), manifesting that OG induced the oxidation of more SH groups to disulfide bonds. Xu et al [35] also concluded that yeast β-glucan accelerated the denaturation of myosin head in the pre-heating stage, meanwhile promoting the re-embedding of the exposed SH groups during the following high temperature heating. In addition, the supplement of ultrasound resulted in a further reduction of SH content ( P < 0.05), which might be because ultrasound promoted the formation of disulfide bonds [36] , resulting in a lower SH content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total SH content significantly decreased after adding OG ( P < 0.05), manifesting that OG induced the oxidation of more SH groups to disulfide bonds. Xu et al [35] also concluded that yeast β-glucan accelerated the denaturation of myosin head in the pre-heating stage, meanwhile promoting the re-embedding of the exposed SH groups during the following high temperature heating. In addition, the supplement of ultrasound resulted in a further reduction of SH content ( P < 0.05), which might be because ultrasound promoted the formation of disulfide bonds [36] , resulting in a lower SH content.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of OG significantly enhanced the hydrophobic interactions of surimi gels ( P < 0.05), and ultrasound could further reinforce the hydrophobic interactions ( P < 0.05). It was speculated that both ultrasound and OG were beneficial to the unfolding of protein structures and the exposure of hydrophobic groups [4] , [35] , thereby strengthening the hydrophobic interactions of proteins. The synergistic effect of ultrasound combined with OG could further strengthen the cross-linking of protein molecules, facilitating the construction of better network structures and higher gel strength and textural characteristics of surimi gels ( Fig.…”
Section: Resultsmentioning
confidence: 99%